PELAKSANAAN PENGANGKATAN ANAK ANTARWARGA NEGARA INDONESIA MENURUT HUKUM ISLAM - Yulies Tiena Masriani (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2011)
Kid's adoption is an effort to take someone else's kid's life into our family, so that between the adopted parent and the adopted kid will impact to a law caution. Kid's adoption between Indonesian based on Islamic Law in order to maintain, educate and fund the kid's life. Then, there will come up problems from adopting the kid among Indonesian due to the Islamic Law. The conclusion is the effort of kid adoption among Indonesian due to Islamic Law is done by a reason that the couple (husband & wife) are not overwhelmed with a kid and also because of self-willingness on choosing gender of the kid, male/female. The adopted kid comes from their own relatives and from other people's kids. As the result of it, the kid doesn't cut off the blood relationship between the adopted kid and the origin family. The relationship between the adopted kid and their adopted parents are bold with a will or called it as wajibah will. The amount of the will or called it as wajibah will for an adopted kid is one-third from the total of the adopted parent's will.